2004
DOI: 10.1001/archinte.164.19.2135
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Use and Health Care Costs of Obese and Nonobese Individuals

Abstract: Over 1 year, health care costs for obese persons are higher than for nonobese persons, primarily because of prescription drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
141
3
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(164 citation statements)
references
References 27 publications
13
141
3
7
Order By: Relevance
“…36 In a retrospective study of 539 obese and 1225 non-obese persons, obese patients had more hospitalizations, prescription drugs, professional claims and outpatient visits. 37 In an earlier analysis of the 1994 National Population Health Survey (NPHS) data, obese people were found to be more likely to consult with physicians, to use more prescribed drugs and to require excess disability days. 38 Using the same NPHS data set, Chen et al 39 found no significant association between obesity and overall hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…36 In a retrospective study of 539 obese and 1225 non-obese persons, obese patients had more hospitalizations, prescription drugs, professional claims and outpatient visits. 37 In an earlier analysis of the 1994 National Population Health Survey (NPHS) data, obese people were found to be more likely to consult with physicians, to use more prescribed drugs and to require excess disability days. 38 Using the same NPHS data set, Chen et al 39 found no significant association between obesity and overall hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Given that sample sizes were sufficient to summarize total visit cost for patients presenting with lead damage in the inpatient setting, we calculated the total hospitalization cost by summing the amount paid to the hospital by the insurer plus coinsurance, copayments, and deductibles paid by the patient. Given the distribution of total hospitalization costs observed, we excluded from cost analyses 19 patients whose total costs fell into the top 5% of the cohort (greater than $73 573 for the PM cohort, $191 042 for ICD, and $296 320 for the CRT‐D cohort) 9, 10, 11, 12. We hypothesized that these patients may have had other major procedures besides just lead revision or repair, resulting in the extreme variance in cost.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that overweight and obesity are associated with increased drug use. [9][10][11][12][13][14][15] Much less information is available on the relation between physical activity levels and use of prescription drugs.…”
Section: Introductionmentioning
confidence: 99%